Genotoxicity of GdVO4:Eu3+ nanoparticles in vitro: an experimental assessment - Tkachenko, A.S.; Prokopiuk, V.Yu.; Onishchenko, A.I.; Yefimova, S.L.; Maksimchuk, P.O.; Klochkov., V.K (Abstract book of International Conference "Nanotechnologies and Nanomaterials"NANO-2022, 2022)
Mutagenic properties are a major challenge to the application of drugs in clinical practice. Any potential drug is tested in the preclinical stage for genotoxicity. Novel nanomaterials, which are promising for use in oncology, infectology and implantology, should be tested for their harmfulness to genetic material. The aim of this study was to evaluate the genotoxicity of gadolinium orthovanadate nanoparticles (GdVO 4 :Eu 3+ ) in vitro. Materials and methods. Genotoxicity studies were performed by the micronucleus assay. The skin fibroblasts of rat fetuses cultivated in DMEM medium with 10% fetal bovine serum in a CO 2 incubator were used after 3 passages. Following transplantation into a 24-well plate at a concentration of 50 000 cells per well, GdVO 4 :Eu 3+ nanoparticles were added at concentrations of 0-30-65-130-260-520 μg / ml. The cells incubated for a short period of time with cisplatin were used as a positive control, while the intact cells were used as a negative control. After 72 hours, the cells were fixed with ethanol, stained according to Romanowsky – Giemsa. The number of cells with micronuclei was identified. Statistical data processing was performed by Kraskel-Wallis and Dunn’s tests. Results. In this study, the genotoxic effect of GdVO 4 :Eu 3+ nanoparticles was evaluated by the micronucleus assay on the culture of fibroblasts and no damaging effect was revealed when using nanoparticles at concentrations of 30-65- 130 μg / ml. The number of cells with micronuclei did not differ from the negative control. At high concentrations, it was technically impossible to perform micronucleus calculations due to loss of cell adhesion and lack of division. In cultures exposed to cisplatin, the number of cells with micronuclei was statistically significantly higher. The cell shape, shape and size of nuclei changed. Conclusions. GdVO 4 :Eu 3+ nanoparticles show no genotoxic effect on fibroblast cultures in vitro.
Keywords: Genotoxicity; GdVO4:Eu3+; nanoparticles; in vitro